Collectin-11 promotes fibroblast proliferation and modulates their activation status and extracellular matrix synthesis - Chen, Wan-Bing; Cao, Bo; Li, Gang; Wang, Gang; Wu, Kun-Yi; Zhang, Ting; Ma, Ning; Zhou, Wuding; Li, Ke (Frontiers in Immunology, 2025)
IntroductionCollectin-11 (CL-11), a recently described soluble C-type lectin, has been shown to stimulate cell proliferation in fibroblasts and melanoma cells. However, its broader influence on fibroblast functions and the specific receptors mediating CL-11's effects remain to be elucidated. MethodsThe EDU proliferation assay and WB detection of PCNA protein levels were used to evaluate the fibroblast proliferative effect after CL-11 stimulated. The qRT-PCR and WB detection of fibronectin and collagen I were used to evaluate the ECM production. The qRT-PCR detection of Il-6, Il-11, Tnfa, Il1b, Cxcl1, Egf, Tgfb1, Pdgfb were used to evaluate the cytokine production. The WB detection of ERK, AKT, STAT3, mTOR, SMAD2 and ACTIN were used to evaluate the activation of signaling pathway. The WB detection of ERK, AKT, STAT3, mTOR, SMAD2 and ACTIN were used to evaluate the activation of signaling pathway. The immunofluorescence and molecular docking experiments were used to detect the binding of CL-11 to EGFR/TGFRII. ResultsIn this study, we demonstrate that CL-11 not only promotes fibroblast proliferation but also modulates their activation status and extracellular matrix (ECM) synthesis. Specifically, treatment with recombinant CL-11 (rCL-11) significantly upregulated the production of ECM proteins (fibronectin, collagen I), growth factors (EGF, TGF-β1), and proinflammatory cytokines/chemokines (IL-6, TNF-α, IL-11, IL-1β, CXCL1) in renal fibroblasts. Additionally, rCL-11 activated multiple intracellular signaling pathways, including ERK, AKT/mTOR, STAT3, and SMAD2. Further, EGFR and TGF-βRII were found to be abundantly expressed in renal fibroblasts, and molecular docking analysis along with immunofluorescence/confocal microscopy confirmed CL-11's interaction with these receptors. DiscussionOur findings provide strong evidence that CL-11 plays a critical role in renal fibroblast proliferation and activation via engagement with EGFR and TGF-βRII, shedding light on the mechanisms by which CL-11 stimulates cellular activation and proliferation.